Efficient modification of the myostatin gene in porcine somatic cells and generation of knockout piglets. Issue 1 (9th November 2015) - Rao, Shengbin; Fujimura, Tatsuya; Matsunari, Hitomi; Sakuma, Tetsushi; Nakano, Kazuaki; Watanabe, Masahito; Asano, Yoshinori; Kitagawa, Eri; Yamamoto, Takashi; Nagashima, Hiroshi
SUMMARY: Myostatin ( MSTN ) is a negative regulator of myogenesis, and disruption of its function causes increased muscle mass in various species. Here, we report the generation of MSTN ‐knockout (KO) pigs using genome editing technology combined with somatic‐cell nuclear transfer (SCNT). Transcription activator‐like effector nuclease (TALEN) with non‐repeat‐variable di‐residue variations, called Platinum TALEN, was highly efficient in modifying genes in porcine somatic cells, which were then used for SCNT to create MSTN KO piglets. These piglets exhibited a double‐muscled phenotype, possessing a higher body weight and longissimus muscle mass measuring 170% that of wild‐type piglets, with double the number of muscle fibers. These results demonstrate that loss of MSTN increases muscle mass in pigs, which may help increase pork production for consumption in the future. Mol. Reprod. Dev. 83: 61–70, 2016. © 2015 Wiley Periodicals, Inc .